Decreased Antithrombin III Activity in Diabetes May Be Due to Non-Enzymatic Glycosylation – A Preliminary Report - Ceriello, A; Russo, P Dello; Zuccotti, C; Florio, A; Nazzaro, S; Pietrantuono, C; Rosato, G B (Thrombosis and Haemostasis, 1983)
Antithrombin III activity was moderately but significantly decreased in insulin dependent diabetics (p <0.005), while no difference has been found between the diabetic (n = 25) and control groups (n = 22) in antithrombin III plasma concentration.Moreover, antithrombin III activity was inversely correlated with glycosylated plasma proteins (r = -0.57; p <0.01).These data show that in diabetes there is a depressed biological activity of antithrombin III and suggest that this reflects nonenzymatic glycosylation of antithrombin III protein.
Keywords: Antithrombin III; Diabetes; Non-enzymatic glycosylation